2020
DOI: 10.1088/1361-6528/abb490
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation ZnS quantum dots into carbon nanotubes for high-performance lithium–sulfur batteries

Abstract: Constructing sulfur hosts with high electronic conductivity, large void space, strong chemisorption, and rapid redox kinetics is critically important for their practical applications in lithium–sulfur batteries (LSBs). Herein, by coupling ZnS quantum dots (QDs) with carbon nanotubes (CNTs), one multifunctional sulfur host CNT/ZnS-QDs is designed via a facile one-step hydrothermal method. SEM and TEM analyses reveal that small ZnS-QDs (<5 nm) are uniformly anchored on the CNT surface as well as encapsulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…5(b)). 61 The lattice spacing of 3.12 Å corresponds to the d (111) plane of ZnS and 3.4 Å corresponds to the d (002) plane of the CNTs, confirming their existence in the composite, as identified in the XRD spectra.…”
Section: Resultssupporting
confidence: 56%
“…5(b)). 61 The lattice spacing of 3.12 Å corresponds to the d (111) plane of ZnS and 3.4 Å corresponds to the d (002) plane of the CNTs, confirming their existence in the composite, as identified in the XRD spectra.…”
Section: Resultssupporting
confidence: 56%
“…ZnS nanodots on MXene nanosheets belonged to cubic structure, with (111), (220), and (311) characteristic peaks located at around 28.9°, 48.5°, and 57.2°, respectively. [ 38 ] The fabricated ZnS/MXene composite films exhibited characteristic peaks of both MXene and ZnS, indicating ZnS nanodots were successfully anchored on MXene nanosheets. The characteristic peaks of ZnS were not obvious in ZM‐A and ZM‐B due to the low ZnS loading and the interlayer structure of the composite film.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have proved that MXene and ZnS could effectively adsorb LiPSs and then suppress the shuttle effect of LiPSs in Li−S batteries. [26,38,51,52] So ZnS/MXene powders obtained by freeze drying in this research were used to modify the surface of separator in Li−S batteries. DFT theoretical calculation revealed the adsorption energy of -F, -OH, and -O on Ti 3 C 2 T x MXene with Li 2 S 6 was −0.83, −3.41, and −1.55 eV, respectively (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6] Comparatively, LSBs have increased extensive focus on global-scale energy storage owing to their large theoretical capacity (1675 mA h g −1 ), high energy density (2600 W h kg −1 ) and advantages of low cost, earth abundance, and environmental friendliness. 7,8 However, there are several challenges toward the commercialization of LSBs: (i) S loss and the shuttle effect due to the dissolution of Li 2 S x (4 < x < 8) into electrolytes, 9 (ii) stability issues resulting from volume expansion/shrinkage during Li insertion/deletion in S, 10 and (iii) low electrical conductivity of sulfur and solid sulfur compounds. 11 These obstructions usually result in low sulfur utilization, sluggish redox kinetics, electrode crack, rapid capacity fading, anode passivation, poor coulombic efficiency, and even a series of safety concerns.…”
Section: Introductionmentioning
confidence: 99%
“…However, C scaffolds can only confine polysulfides physically because of the weak nonpolar interaction between polysulfides and C. 20 Many efforts have been devoted to exploring highly conductive S hosts combined with polarity. Recent research studies have demonstrated that coupling C scaffolds with metal oxides/sulfides, such as ZnO, 21 V 2 O 5 , 22 ZnS, 7 and CoS 2 , 23 can effectively chemisorb polysulfides and mitigate the shuttle effect. These approaches do improve the capacity and cycling stability of LSBs.…”
Section: Introductionmentioning
confidence: 99%